Fundamental Factors and Capital Behavior of Banking in Indonesia - Sangadah, Dhurotus (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
Capital has an important role in banking operations, in addition to indicating the fulfillment of capital regulations also serves to anticipate future risks. Studies of ROA-mediated capital buffers are still rare. This study aims to investigate the role of return on assets as mediation on the influence of loans to total assets (LOTA) and non performing loans (NPL) on capital buffers. This study is conducted by using path analysis research conducted on commercial banks owned by the government with an observation period from 2015 to 2020. The existence of interference, especially on the funding side, is one of the characteristics of the company's bank. The results showed that lota negatively affects ROA and capital buffer while NPL negatively affects ROA and positively affects capital buffer. In roa mediation testing is able to mediate the influence of NPL on capital buffers but is not able to mediate LOTA's engaruh against capital buffers.